Developing Rural Tourism with the Participation of Related Parties in Bac Kan Province - Nuong, Le Ngoc; Trang, Ngo Thi Huyen; Trang, Nguyen Thi Thuy; Lam, Nguyen Tien (Journal La Bisecoman, 2021)
Tourism development policy will pay attention to stakeholders, especially the people, who play an important role. However, in reality, when people participate in rural tourism development, they are not equipped with basic knowledge and skills in managing and serving tourists. Because the benefits between stakeholders are still not clear, the participation of people in rural tourism development is currently only passive. Active participation need to be directed from the Government and local authorities because the concept that rural tourism development is not only about creating economic benefits but also associated with conservation and preservation, together with keeping and promoting cultural - historical values in rural areas.